Effect of a "dance to health" model on the level of physical activity, time spent watching television, food consumption rate, and stages of change in female adolescents in ninth year - Hernández Quesada, Óscar (2010)
The aim of this study was to determine the influence of a health promotion program called " Dance to Health" under the Transtheoretical Model as a basis for intervention, Latin dance (as a form of physical exercise) and talks regarding food and physical activity on the time spent watching television, frequency of food consumption, and stages of change.  A total of 66 female adolescents participated in the study; 33 were in the experimental group and 33 in the control group.  Participants were high school students aged between 15 and 17.  The program lasted 12 weeks, with one 80-minute session per week.  An initial pretest was administered, which yielded the amount of time devoted to performing physical activity (TPA), time spent watching television (TWT), food consumption rate (FCR), both healthy and unhealthy (ENCA 1997-98) and where the group was located within the stages of change (SC).  At the end, a post-test was performed to verify the changes perceived after treatment.  Statistical analysis: in order to determine the effect of the intervention on TPA, TWT, FCR, and SC, a two-way ANOVA was used and data was analyzed using the SPSS statistical package version 10. Results: regarding the TPA variable, the experimental group increased significantly in minutes, while the control group decreased the time used to perform physical activity (p <0.01).  On the other hand, in the TWT variable, the experimental group significantly decreased compared to the control group, which increased the TWT (p <0.01). In the case of SC, the results were generally favorable for the experimental group, unlike the control group whose behavior showed negative trends.  Finally, in the FCR variable no significant changes were observed in the average consumption of food groups analyzed. Conclusions: The program was able to create behavioral changes in the TPA, TWT, FCR and SC variables.